Sistem Penjaminan Mutu Perpustakaan Institut Agama Islam Nasional Laa Roiba - Agus Suryana; Qowaid Qowaid; Heni Feviasari (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
The university library is an information center for students and lecturers in the academic community. In carrying out its role in providing services to users, libraries must be able to develop and improve the quality of libraries for users. To find out how far the library is going well or not, the library must evaluate it by analyzing the quality of the library using the SWOT method. This method can find out how big the role of the library in improving quality. This quality improvement plays a very important role for the library. So that the realization of a quality and standardized library in accordance with the standards of a university library. SWOT analysis includes internal and external factors which can measure the progress and age of a library. This study maps the external environmental factors and the library's internal environment, where the external factors in question are threats or opportunities that can be obtained by the current library for the development process. In addition, internal factors are the strengths and weaknesses of the library. Based on the SWOT matrix, internal strength factors have a high point with a value of 4 which is very good, for weaknesses it has a value of 3 which is good and external factors opportunity has a value of 4 which is very good and threats have a value of 3 which is good, thus it can be seen SWOT position in the growth quadrant on the internal factor rating of 3.5 and the growth quadrant position on the external factor rating of 3.5. Keywords: Quality Assurance, SWOT, Library, Quality